Una relectura de la hospitalidad levinasiana para nuestros tiempos violentos - Alanís Noyola, Paul Henri (Universidad Michoacana de San Nicolás de Hidalgo, 2019)
Throughout this dissertation, we will establish the critical consequences of the philosophical corpus of Emmanuel Levinas, through the optics of their convergence with the violence of our flesh-and-blood world, at the crucible where human choice becomes entangled with the chaos of error and uncertainty. I will present a few points up for the consideration of the reader that can be faithfully surmised from a reading of levinasian philosophy, which are contributions from complementary authors as well as myself. The radical otherness of the neighbor, because of his resistance to totalization, makes up a traumatic event that cannot be assumed as solely beneficial for the subject. Thus, the encounter with the neighbor constitutes an encounter with what is deinós, or disquieting. This would imply that every action directed at the other will be bound to the risk of performing violence upon him, which would constitute the encounter with the other as an aporia par excellence. Furthermore, any attempt to form a community with the neighbor will surge from the trepidation and uncertainty stemming from welcoming the inscrutable otherness of the other. Conversely, the radical deference towards the other, implicit within levinasian hospitality, once it is applied to the social concerns of our time, ought to be taken with hesitation when considering it as a series of universal, prescriptive axioms particularly when we take into account marginalized social groups.

Durante el curso de este trabajo de tesis estableceremos las consecuencias graves de la filosofía de Emmanuel Levinas desde su convergencia con la violencia de nuestro mundo de carne-y-hueso, cuando la decisión humana se mezcla con el caos del error y la incertidumbre. Expondré algunos puntos a consideración del lector que se desprenden fielmente a partir de la lectura de la filosofía levinasiana, pero que también constituyen aportes de reflexión y crítica por parte de autores complementarios y por parte mía. La otredad radical del prójimo, por su resistencia a la totalización, constituye un evento traumático que no puede ser asumido como unívocamente benévolo por el sujeto. Por tanto, el encuentro con el prójimo es un encuentro con lo deinós, lo inquietante. Suponemos, entonces, que toda acción que se dirige hacia el otro estará atada al riesgo de ejercer violencia sobre él, lo que por lo tanto constituirá el encuentro con el otro como la aporía por excelencia. Empero, cualquier intento de entablar comunidad con el prójimo partirá de la trepidación y la incertidumbre de darle la bienvenida a la otredad inescrutable del otro. Ahora bien, la deferencia radical hacia el otro, implícita en la hospitalidad levinasiana, una vez aplicada a temáticas sociales de nuestra época, deberá considerarse con reticencia ante el prospecto de asumirse como prescripciones axiomáticas aplicables en todos los contextos y para todas las personas, especialmente cuando hablemos de grupos marginados.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2019-1857; Otredad; Levinas; Aporía; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1639